Binded hybrid polymer non-porous particles and their use
By using surface-modified non-porous polymer cores, non-porous organic-inorganic hybrid materials and bonding materials, the problem of unstable existing chromatographic stationary phases at high pH is solved, and high resolution separation and stable chromatographic performance of large biomolecules are achieved.
Patent Information
- Application Number
- CN202380061253.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-26
- Filing Date
- 2023-02-24
- Publication Date
- 2025-04-04
AI Technical Summary
The existing chromatographic stationary phase is unstable at high pH, making it difficult to achieve high resolution separation of large biological molecules.
Nonporous composite particles including surface-modified nonporous polymer cores, nonporous organic-inorganic hybrid materials and bonding materials in contact with them are used to ensure stability at high pH and improve separation efficiency of large biomolecules.
Chromatographic separation maintained stable at high pH is achieved, retention time is extended, peak shape and separation efficiency is improved, and is especially suitable for high resolution separation of large biomolecules.
Smart Images

Figure BDA0005280784290000221 
Figure HDA0005280784300000011 
Figure HDA0005280784300000012
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to and the benefit of U.S. Provisional Application Serial No. 63 / 401,494, entitled “Bonded Hybrid Polymer Non-Porous Particles And Their Use For Bioseparations,” filed on August 26, 2022. The entirety of the aforementioned application is incorporated herein by reference. Technical Field
[0003] The present technology relates to chromatographic materials. More specifically, the present technology relates to nonporous composite particles for chromatographic separation. Generally speaking, the nonporous composite particles include a surface-modified nonporous polymer core, a nonporous organic-inorganic hybrid material in contact with the surface-modified core, and a bonding material in contact with the nonporous organic-inorganic hybrid material. Some embodiments are characterized by a nonporous composite particle including a nonporous polymer core modified with a bonding material. Background Art
[0004] Chromatography is a separation method involving two phases, one being the stationary phase and the other being the mobile phase. Typically, the stationary phase is porous or non-porous particles packed into a column. The mobile phase flows through the packed column. The sample or analyte to be separated is injected at the beginning of the column and is transported through the system by the mobile phase. As they pass through the column, the different components of the sample are distributed according to their relative affinities for the two phases. The results of the chromatographic separation are then depicted via a chromatogram, where the sample components can be identified by the various peaks or patterns in the chromatogram.
[0005] Measuring the degree of separation between two components is often referred to as the resolution of each component. Resolution can be determined by the efficiency, selectivity, and retention of the separation process. Efficiency refers to the quality of separation of the sample components and is usually determined by the number of separable peaks in the chromatogram. Selectivity refers to the ability of the chromatography to separate the sample components and is usually measured by the retention ratio of the two peaks in question in the chromatogram and can be visualized as the distance between the apexes of the two peaks. Retention or retention time refers to the time it takes for a sample to pass through the chromatographic column and is usually measured as the time interval between the injection of the sample and the detection of its components on the chromatogram.
[0006] Adjusting the mobile phase pH is a powerful tool to improve the retention and selectivity of analytes, especially ionizable analytes, in chromatographic separations. In reversed-phase chromatographic separations of basic compounds, peptides, and biological samples, high pH mobile phases combined with high temperatures are often used to obtain extended retention, excellent peak shape, and good efficiency. Silica-based stationary phases have been preferred in the past due to their stability at neutral pH and high temperatures. However, a common disadvantage is that silica-based stationary phases are unstable at high pH due to dissolution-induced particle corrosion, which in turn limits its use in these applications. An alternative to silica-based stationary phases is to use polymer-based stationary materials. Polymer-based stationary particles have shown some promise, but also have some limitations in the choice of the desired surface chemistry.
[0007] Mass transfer and lateral diffusion properties are extremely important in high resolution separations of large biomolecules. However, in the separation of large biomolecules, the diffusion path that the analyte must traverse between the nonporous stationary phase and the mobile phase is very short, and the column efficiency becomes independent of the flow rate. Therefore, there is a need for nonporous particles used as stationary phases that have the ability to remain stable at high pH and to obtain high resolution separations of large biomolecules. Summary of the invention
[0008] The present technology relates to non-porous composite particles for chromatographic separations. In particular, embodiments of the present technology relate to chromatographic separations of large biomolecules.
[0009] In general, the technology disclosed herein relates to nonporous composite particles. In one embodiment, the present technology relates to a nonporous composite particle, which includes a surface-modified nonporous polymer core, a nonporous organic-inorganic hybrid material in contact with the surface-modified nonporous polymer core, and a bonding material in contact with the nonporous organic-inorganic hybrid material. That is, the embodiments of the present disclosure relate to a nonporous composite particle, which includes a nonporous polymer particle core with a modified surface, a nonporous organic-inorganic hybrid material in contact with the modified surface, and a bonding material in contact with the nonporous organic-inorganic hybrid material. In certain embodiments, the modified surface is a silyl-modified surface including a first functional group and a second functional group. In certain embodiments, the nonporous organic-inorganic hybrid material is modified with a bonding material. Due to the use of such nonporous particles in the stationary phase of chromatographic separation, the nonporous particles are able to remain stable at high pH, and obtain large biomolecules (such as hydrodynamic radii exceeding Some even exceed high resolution separation of those biomolecules).
[0010] In another embodiment, the present technology is directed to a nonporous composite particle including a silyl-modified nonporous polymer core. A binding material is applied to the silyl-modified surface to provide functional groups to the nonporous composite particle.
[0011] In one aspect, the present technology is directed to a nonporous composite particle comprising a nonporous polymer particle core having a silyl-modified surface, a nonporous organic-inorganic hybrid material in contact with the silyl-modified surface, and a binding material in contact with the nonporous organic-inorganic hybrid material.
[0012] The above aspects may include one or more of the following features. In some embodiments, the nonporous polymer particle core of the nonporous composite particles includes 80% divinylbenzene. In some embodiments, at least a portion of the nonporous organic-inorganic hybrid material is bonded to the silyl-modified surface of the nonporous particle core through silane bonding. In some embodiments, at least a portion of the nonporous organic-inorganic hybrid material is a silane to form a functionalized surface. In some embodiments, the functionalized surface of the nonporous organic-inorganic hybrid material is hydrophilic. In some embodiments, the silane includes a hydroxyl-terminated polyethylene glycol (HO-PEG) silane. In some embodiments, at least a portion of the nonporous organic-inorganic hybrid material is an alkyl silane to form a functionalized surface. In some embodiments, the functionalized surface of the nonporous organic-inorganic hybrid material is hydrophobic. In some embodiments, at least a portion of the nonporous organic-inorganic hybrid material is an ionizable silane to form a functionalized surface. In some embodiments, the functionalized surface of the nonporous organic-inorganic hybrid material is charged. In some embodiments, the silyl-modified surface of the nonporous polymer particle core comprises a first functional group and a second functional group, the first functional group comprises a reactive silane, and the second functional group comprises an organic polymerizable group. In some embodiments, the reactive silane comprises an alkoxy group. In some embodiments, the organic polymerizable group comprises a vinyl group.
[0013] In another aspect, the present technology is directed to a nonporous particle including a nonporous polymer particle core having a silyl-modified surface and a binding material in contact with the silyl-modified surface of the nonporous polymer particle core.
[0014] The above aspects may include one or more of the following features. In some embodiments, the nonporous polymer particle core of the nonporous composite particles includes divinylbenzene (80%). In some embodiments, at least a portion of the bonding material is bonded to the modified surface of the nonporous particle core through silane bonding. In some embodiments, at least a portion of the bonding material is a silane to form a functionalized surface. In some embodiments, the functionalized surface is hydrophilic. In some embodiments, at least a portion of the bonding material is an alkyl silane to form a functionalized surface. In some embodiments, the functionalized surface of the bonding material is hydrophobic. In some embodiments, at least a portion of the bonding material is an ionizable silane to form a functionalized surface. In some embodiments, the functionalized surface of the bonding material is charged. In some embodiments, the silyl-modified surface of the nonporous polymer particle core includes a first functional group and a second functional group, the first functional group includes a reactive silane, and the second functional group includes an organic polymerizable group. In some embodiments, the reactive silane includes an alkoxy group. In some embodiments, the organic polymerizable group includes a vinyl group.
[0015] The present technology provides many advantages over current chromatographic separation methods. For example, the use of the nonporous composite particles described herein can provide high resolution separations of large biomolecules. That is, a nonporous polymer particle core comprising a silyl-modified surface, a nonporous organic-inorganic hybrid material in contact with the silyl-modified surface, and a bonding material in contact with the nonporous organic-inorganic hybrid material can provide better separations of large biomolecules than the methods currently used in the industry. The present technology can remain stable at high pH. Therefore, chromatographic separations using the nonporous composite particles described herein can result in extended retention, better peak shape, and more effective separations of large biomolecules. BRIEF DESCRIPTION OF THE DRAWINGS
[0016]
[0008] The foregoing features and advantages and other features and advantages provided by the present technology will be fully understood from the following description of exemplary embodiments when read in conjunction with the accompanying drawings.
[0017] Those skilled in the art will appreciate that the drawings are primarily for illustrative purposes and are not intended to limit the scope of the inventive subject matter described herein. The drawings are not necessarily drawn to scale; in some cases, various aspects of the inventive subject matter disclosed herein may be exaggerated or enlarged in the drawings to facilitate understanding of different features. In the drawings, the same reference numerals generally represent the same features (e.g., functionally similar and / or structurally similar elements).
[0018] Figure 1A is a schematic cross-sectional view of a non-porous composite particle according to one embodiment of the present disclosure.
[0019] Figure 1B yes Figure 1AMagnified view of a portion (BB) of a non-porous composite particle.
[0020] Figure 2A is a schematic cross-sectional view of a non-porous composite particle according to another embodiment of the present disclosure.
[0021] Figure 2B yes Figure 2A Magnified view of a portion (CC) of a non-porous composite particle.
[0022] Figure 2C is an enlarged view of another embodiment of a portion (CC) of a non-porous composite particle.
[0023] Figure 3A is a schematic cross-sectional view of a non-porous composite particle according to another embodiment of the present disclosure.
[0024] Figure 3B yes Figure 3A Magnified view of a portion (DD) of a non-porous composite particle.
[0025] Figure 4A is a schematic cross-sectional view of a non-porous composite particle according to another embodiment of the present disclosure.
[0026] Figure 4B yes Figure 4A Magnified view of a portion (EE) of a non-porous composite particle.
[0027] Figure 5 is a schematic diagram of the flow dynamics according to Example 2.
[0028] Figure 6 is a chromatogram of the barrier chromatography separation of nuclease-treated lambda phage DNA described in Example 3.
[0029] Fig. 7A is another chromatogram and gel electrophoresis results of the barrier chromatography separation of nuclease-treated lambda phage DNA described in Example 3.
[0030] Figure 7B is a chromatogram of the barrier chromatography separation of untreated lambda phage DNA described in Example 3.
[0031] Figure 8 This is the ion-pairing reverse phase chromatogram of 20mer to 100mer deoxythymidine oligomers obtained in Example 4.
[0032] Fig. 9 is a chromatogram of the separation described in Example 5. DETAILED DESCRIPTION
[0033] The present disclosure relates to nonporous composite particles, which include a nonporous polymer particle core having a modified surface (e.g., a silyl-modified surface), a nonporous organic-inorganic hybrid material in contact with the modified surface, and a bonding material in contact with the nonporous organic-inorganic hybrid material. That is, embodiments of the present disclosure relate to a nonporous particle, which includes a surface-modified nonporous polymer (e.g., organic material) particle core, an organic-inorganic hybrid nonporous material in contact with the modified surface, and a bonding material in contact with the nonporous organic-inorganic hybrid material and / or the modified surface. In some embodiments, the modified surface is a silyl-modified surface comprising a first functional group (i.e., a reactive silane) and a second functional group (i.e., an organic polymerizable group).
[0034] like Figure 1A As shown in FIG. 3C , nonporous particles (100; 200; 300) according to embodiments of the present disclosure are provided. Nonporous particles (100; 200; 300), nonporous polymer particle cores (110; 210; 310), modified surfaces (120; 220; 320) of nonporous polymer particle cores (110; 210; 310), organic-inorganic hybrid nonporous materials (130; 230; 330) around the modified surfaces (120; 220; 320), and bonding materials (140; 240; 340). The organic-inorganic hybrid nonporous material (130; 230; 330) can be deposited or grown on the modified surfaces (120; 220; 320). The modified surface (120; 220; 320) and / or the organic-inorganic hybrid non-porous material (130; 230; 330) may include a binding material (140; 240; 340).
[0035] The non-porous particles of the present disclosure are generally spherical. The diameter of the non-porous particles of the present disclosure is typically in the range of 1 micron to 14 microns, more typically in the range of 1 micron to 6 microns. The particle diameter is measured herein by dispersing the sample in methanol containing 5% lithium chloride using a Coulter counter (Beckman Coulter, Multisizer 4e Coulter Counter, Brea, CA, USA). For each sample, a count of more than 70,000 particles was run using a 30 μm hole in volume mode. Using the Coulter principle, the volume of the particle is converted into a diameter, wherein the particle diameter is an equivalent spherical diameter, and the equivalent spherical diameter is the diameter of a sphere having the same volume as the volume of the particle. The particle diameter is measured as the 50% cumulative diameter of the particle size distribution based on volume.
[0036] In some embodiments, the nonporous particles of the present disclosure have good stability even at pH greater than 12 and less than 1. For example, in embodiments, nonporous particles according to the present technology exhibit less than 4% weight loss after exposure to an aqueous solution at a pH of 12.3 for 12 hours. Columns filled with these nonporous particles and exposed to alkaline conditions show minimal loss in separation performance.
[0037] The nonporous particles of the present disclosure are also generally narrowly distributed in size. As defined herein, a collection of particles is "narrowly distributed in size" when the ratio of the 90% cumulative volume diameter divided by the 10% cumulative volume diameter is less than 1.4 when measured with a Beckman Coulter, Multisizer 4e Coulter Counter.
[0038] Nonporous polymer core .
[0039] The polymer particle core used in the present disclosure comprises at least one organic polymer. The organic polymer core typically contains greater than 95% organic polymer, more typically greater than 97.5% organic polymer, and even more typically greater than 99% organic polymer.
[0040] The polymer particle core is non-porous, which is defined herein to mean that the polymer particle core has a pore volume of less than 0.1 cc / g. Preferably, in some embodiments, the organic polymer core has a pore volume of less than 0.1 cc / g (e.g., 0.05 cc / g), preferably less than 0.02 cc / g. The pore volume is determined based on a multi-point nitrogen adsorption experiment (Micromeritics ASAP 2400; Micromeritics Instruments Inc., Norcross, GA) using methods known in the art.
[0041] The diameter of the polymer core is typically in the range of, for example, 1 micron to 10 microns, more typically 1 micron to 5 microns. The polymer core is generally of narrow size distribution.
[0042] Basically, the polymer particle cores for use in the present disclosure include those composed of carbon and hydrogen, those composed of carbon, hydrogen and oxygen, those composed of carbon, hydrogen and nitrogen, and those composed of carbon, hydrogen, nitrogen and oxygen. The backbone of the organic polymer chain forming the polymer core may contain CC, CO, CN and / or ON covalent bonds. In some embodiments (e.g., in the case of polymers formed by free radical polymerization of vinyl groups), the backbone of at least one organic polymer chain may contain only CC covalent bonds.
[0043] As mentioned above, the polymer core for the present disclosure comprises at least one organic polymer. The at least one organic polymer comprises the residues of one or more organic monomers. The one or more organic monomer residues forming the at least one organic polymer may be selected from the residues of hydrophobic organic monomers, the residues of hydrophilic organic monomers, or a mixture of the residues of hydrophobic organic monomers and the residues of hydrophilic organic monomers.
[0044] The hydrophobic organic monomer may be selected from, for example, C2-C18 olefin monomers and / or monomers including C6-C18 monocyclic or polycyclic carbocyclic groups (e.g., phenyl groups, phenylene groups, naphthalene groups, etc.). Specific examples of hydrophobic organic monomers include, for example, monofunctional and polyfunctional aromatic monomers such as styrene, alkyl-substituted styrene, halogen-substituted styrene, divinylbenzene, and vinylbenzyl chloride; monofunctional and polyfunctional olefin monomers such as ethylene, propylene, or butylene; monofunctional and polyfunctional fluorinated monomers such as vinyl fluoride, 1,1-(difluoroethylene), tetrafluoroethylene, trifluorochloroethylene, hexafluoropropylene, perfluoropropyl vinyl ether, or perfluoromethyl vinyl ether; monomers having higher alkyl or carbon atoms; Monofunctional or multifunctional acrylate monomers having a cyclic group, for example, a monofunctional or multifunctional acrylate monomer having a C6-C18 alkyl, alkenyl or alkynyl group or a C6-C18 saturated, unsaturated or aromatic carbocyclic group; monofunctional or multifunctional methacrylate monomers having a higher alkyl or carbocyclic group, for example, a monofunctional or multifunctional methacrylate monomer having a C6-C18 alkyl, alkenyl or alkynyl group or a C6-C18 saturated, unsaturated or aromatic carbocyclic group, and the like.
[0045] The hydrophilic organic monomer can be selected from, for example, a monofunctional or multifunctional organic monomer having an amide group, a monofunctional or multifunctional organic monomer having an ester group, a monofunctional or multifunctional organic monomer having a carbonate group, a monofunctional or multifunctional organic monomer having a carbamate group, a monofunctional or multifunctional organic monomer having a urea group, a monofunctional or multifunctional organic monomer having a hydroxyl group, and a monofunctional or multifunctional organic monomer having a nitrogen-containing heterocyclic group, etc. Specific examples of the hydrophilic organic monomer include, for example, vinyl pyridine, N-vinyl pyrrolidone, N-vinyl piperidone, N-vinyl caprolactam, lower alkyl acrylates (e.g., methyl acrylate, ethyl acrylate, etc.), lower alkyl methacrylates (e.g., methyl methacrylate, ethyl methacrylate, etc.), vinyl acetate, acrylamide or methacrylamide monomers, hydroxypolyethoxy allyl ether monomers, ethoxyethyl methacrylate, glycidyl methacrylate, ethylene glycol dimethacrylate, methylenebisacrylamide, allyl methacrylate, or diallyl maleate.
[0046] In various embodiments, the nonporous polymer core includes residues of a multifunctional hydrophobic organic monomer such as divinylbenzene and / or a multifunctional hydrophilic organic monomer such as ethylene glycol dimethacrylate, methylenebisacrylamide, or allyl methacrylate to provide crosslinking in the organic copolymer. In certain embodiments, DVB 80 may be employed, which is an organic monomer mixture comprising divinylbenzene (80%) and a mixture of ethyl-styrene isomers, diethylbenzene, and may also include other isomers.
[0047] In various embodiments, the polymer core may include only residues of multifunctional organic monomers. In various embodiments, the polymer may include residues of both multifunctional organic monomers and monofunctional organic monomers.
[0048] The present inventors have discovered that in some embodiments, the porosity of a material formed from a polymer containing multifunctional organic monomer residues can be reduced by adding monofunctional organic monomer residues to the polymer, or the porosity of a material formed from a polymer containing multifunctional organic monomer residues and monofunctional organic monomer residues can be reduced by increasing the amount of monofunctional organic monomer residues relative to the multifunctional organic monomer residues in the polymer. For example, it has been found that a polymer particle core formed from DVB 80 (which is formed from an organic polymer containing 80% multifunctional divinylbenzene monomer residues and monofunctional ethylstyrene monomer residues, as described above) has a porosity of about 0.015 cc / g, while an organic polymer core formed from DVB 80 and styrene (which contains multifunctional divinylbenzene monomer residues, monofunctional ethylstyrene monomer residues, and additional monofunctional styrene monomer residues) has a porosity of less than 0.007 cc / g.
[0049] In some embodiments, a polymer particle core is produced, wherein the central region of the core is formed by an organic copolymer containing a multifunctional organic monomer residue and a monofunctional organic monomer residue, and the outer region of the core is formed by an organic homopolymer containing only a multifunctional organic monomer residue. In some embodiments, an organic polymer core is produced, wherein the central region of the core is formed by an organic copolymer containing a multifunctional organic monomer residue and a monofunctional organic monomer residue, and the outer region of the core is also formed by an organic copolymer containing a multifunctional organic monomer residue and a monofunctional organic monomer residue, but wherein the molar ratio of the multifunctional organic monomer residue in the outer core region to the monofunctional organic monomer residue is increased relative to the central core region. In a specific example, an organic polymer core is produced, wherein the central region of the core is formed by DVB and styrene, and the outer region of the core is formed by DVB. In other embodiments, relative to the central core region, the molar ratio of the multifunctional organic monomer residue in the outer core region to the monofunctional organic monomer residue is reduced.
[0050] In various embodiments, the entire polymer particle core may be formed from an organic polymer comprising residues of a multifunctional organic monomer but not residues of a monofunctional organic monomer. In various embodiments, the entire polymer particle core may be formed from an organic polymer comprising residues of both multifunctional organic monomers and monofunctional organic monomers.
[0051] The polymer forming the polymer particle core can be prepared by a variety of methods and mechanisms, including, but not limited to, chain addition and stepwise condensation methods, free radical, anionic, cationic, ring opening, group transfer, metathesis, and photochemical mechanisms. In a particularly advantageous embodiment, the nonporous polymer particle core is prepared via free radical polymerization.
[0052] In some embodiments, the polymer particle core of the present disclosure can be prepared by a dispersion polymerization method, in which a homogeneous solution is formed, wherein monomers, initiators, and stabilizers are combined in a solvent or solvent mixture. As the polymerization proceeds, the initially formed polymer precipitates out of the homogeneous solution to form precipitated nuclei. The formed precipitated nuclei still carry reactive sites, such as free radicals, which allow them to keep growing by continuously capturing and incorporating monomers and / or oligomers from the solution.
[0053] In an exemplary method based on free radical polymerization, one or more solvents and one or more stabilizers are purged with nitrogen to remove dissolved oxygen. Then, one or more monomers (including at least one multifunctional monomer) and a free radical polymerization initiator are added. Usually, under stirring, free radical polymerization is initiated by increasing the temperature for several hours. Based on the desired particle diameter, additional free radical polymerization initiators and additional monomers can be added to the reaction mixture to allow the particles to further grow to the desired size. After the reaction, the particles can be thoroughly washed and dried under vacuum.
[0054] Any free radical initiator compatible with the organic phase can be used alone or in a mixture of such free radical initiators. In a specific embodiment, the free radical initiator can be thermally activated or photoactivated. In a specific embodiment, the free radical initiator is a peroxide, peracetic acid, persulfate, azo initiator or a mixture thereof.
[0055] In the case where the initiator is a thermal initiator, the resulting solution can then be heated to an elevated temperature with stirring to activate the thermal initiator and maintained at the elevated temperature until polymerization is complete. In the case where the initiator is a photoinitiator, the resulting solution can then be irradiated with light of a suitable wavelength with stirring to activate the photoinitiator and maintained until polymerization is complete. Suitable organic monomers for the organic phase are as described above.
[0056] Solvent systems used to form polymer particle cores include methanol, ethanol, isopropanol, 2-methoxyethanol, water, acetonitrile, p-xylene, and toluene.
[0057] Stabilizers that can be used to form the polymer particle core include, for example, polyvinyl pyrrolidone (PVP); nonionic surfactants, including alkylphenol ethoxylates (e.g., Triton™ N-57, available from Dow Chemical); polyvinyl alcohol (PVA), such as Selvol TM Polyvinyl alcohol solution (available from Sekisui Special Chemicals); modified celluloses, including alkyl-modified celluloses such as methyl cellulose (e.g. Methocel TM , available from DuPont); and a hydrophobically modified cellulose hydroxyethyl cellulose stabilizer, such as Natrosol TM cetyl modified hydroxyethyl cellulose (available from Ashland); and ionic surfactants, including sodium alkyl sulfates, such as sodium dodecyl sulfate (SDS) and sodium oleyl sulfate, and the like.
[0058] In a specific embodiment of the nonporous polymer particle core formation, the monomers are a combination of DVB and styrene, the initiator is 2,2'-azobis(2-methylpropionitrile) (AIBN), the solvent system is a combination of reagent alcohol and p-xylene, and the stabilizer is polyvinylpyrrolidone (PVP 40).
[0059] Once formed, the organic polymer core may contain surface moieties from which further polymerization may be carried out. For example, nonporous polymer particle cores formed by free radical polymerization typically contain residual free radical polymerizable unsaturated surface moieties (e.g., ethylenyl moieties, vinyl moieties, methacryloxy moieties, or acryloxy moieties, etc.) from which further core growth may be carried out. Such further polymerization may be used to increase the size of a given batch of polymer particle cores by adding additional thickness of nonporous organic polymer to previously formed nonporous polymer particle cores.
[0060] In a specific embodiment of nonporous polymer particle core growth, the monomer is DVB, the solvent is reagent alcohol, and the stabilizer is polyvinylpyrrolidone (PVP 40).
[0061] Surface modified nonporous polymer core .
[0062] In some embodiments, the present application relates to nonporous polymer particles with modified surfaces. In some embodiments, the modified surface of the nonporous polymer particles can form covalent bonds or electrostatic bonds with the nonporous organic-inorganic hybrid material subsequently applied. In certain embodiments, the modified surface of the nonporous polymer core is a silyl-modified surface. The silyl-modified surface comprises a first functional group and a second functional group. For example, the first functional group is a reactive silane (e.g., an alkoxy group), and the second functional group is an organic polymerizable group (e.g., a vinyl group).
[0063] In some embodiments, the modified surface of the nonporous polymer particle core may have a thickness in the range of 1 nm to 300 nm, for example, any thickness in the range of 1 nm to 3 nm to 10 nm to 30 nm to 100 nm to 300 nm (i.e., in a range between any two of the foregoing values).
[0064] In some embodiments, the modified surface includes a surface polymer, which may include a functional group covalently bonded or electrostatically bonded to an organic-inorganic hybrid nonporous material. Examples of functional groups electrostatically bonded to organic-inorganic hybrid nonporous materials include amide functional groups and amine functional groups. In this regard, the organic-inorganic hybrid materials described herein are weakly acidic in nature, and therefore tend to be deprotonated and negatively charged, while the amide functional groups or amine functional groups described herein are basic in nature, and therefore tend to be protonated and positively charged. Examples of functional groups covalently bonded to nonporous organic-inorganic hybrid materials include organosilane functional groups and organometallic functional groups, such as organotitanium functional groups and organozirconium functional groups. As used herein, an organosilane functional group is a functional group having at least one Si-C bond. Similarly, an organotitanium functional group is a functional group having at least one Ti-C bond, and an organozirconium functional group is a functional group having at least one Zr-C bond.
[0065] In some embodiments, the modified surface includes a surface polymer that may include monomer residues covalently or electrostatically bonded to a nonporous organic-inorganic hybrid material. Examples of monomer residues electrostatically bonded to a nonporous organic-inorganic hybrid material include amide monomer residues and amine monomer residues. Examples of monomer residues covalently bonded to a nonporous organic-inorganic hybrid material include organosilane monomer residues, organotitanium monomer residues, and organozirconium monomer residues. As used herein, an organosilane monomer residue is a monomer residue having at least one Si-C bond, an organotitanium monomer residue is a monomer residue having at least one Ti-C bond, and an organozirconium monomer residue is a monomer residue having at least one Zr-C bond.
[0066] The surface polymer may comprise, for example, polymer chains grafted onto a nonporous polymer core.
[0067] The surface polymer may comprise, for example, a cross-linked polymer network formed on a non-porous polymer particle core.
[0068] The surface polymers can be prepared by a number of methods and mechanisms including, but not limited to, chain addition and stepwise condensation methods, free radical, anionic, cationic, ring opening, group transfer, metathesis, and photochemical mechanisms. In particularly advantageous embodiments, the nonporous organic polymer core is prepared via free radical polymerization.
[0069] As mentioned above, the polymer particle core may contain surface moieties from which further polymerization may be carried out. For example, organic polymer cores formed by free radical polymerization typically contain residual free radical polymerizable unsaturated surface moieties (e.g., ethylenyl moieties, vinyl moieties, methacryloxy moieties, acryloxy moieties, etc.) from which polymerization of surface polymers may be carried out. The polymer chains may be derived from monofunctional monomers. The crosslinked polymer network may be formed from multifunctional monomers. In addition to multifunctional monomers, monofunctional monomers may also be included in such crosslinked polymer networks.
[0070] As described above, surface polymers include those comprising amide monomer residues. Examples of amide monomer residues include amide monomer residues having the formula: wherein n is an integer from 1 to 3 (i.e., N-vinylpyrrolidone, N-vinyl-2-piperidone, or N-vinylcaprolactam). Examples of amide monomer residues also include those having the formula An amide monomer residue, wherein R1 is selected from C1-C6 alkylene, C2-C6 alkenylene, C2-C6 alkynylene, C6-C18 arylene, and wherein R2 is selected from H, C1-C6 alkylene, C2-C6 alkenylene, C2-C6 alkynylene, C6-C18 arylene.
[0071] As also described above, surface polymers include those comprising amine monomer residues. Examples of amine monomer residues include aminoalkyl acrylates, aminoalkyl methacrylates, dialkylaminoalkyl acrylates, or dialkylaminoalkyl methacrylates, including amino-C1-C4-alkyl acrylates, amino-C1-C4-alkyl methacrylates, di-C1-C4-alkylamino-C1-C4-alkyl acrylates, di-C1-C4-alkylamino-C1-C4-alkyl methacrylates, such as 2-aminoethyl acrylate, 2-aminoethyl methacrylate, 2-(N,N-dimethylamino)ethyl acrylate, 2-(N,N-dimethylamino)ethyl methacrylate, 2-(N,N-diethylamino)ethyl methacrylate, or 2-diisopropylaminoethyl methacrylate.
[0072] As further described above, examples of surface polymers also include those comprising silane monomer residues electrostatically bonded to the nonporous organic-inorganic hybrid material. In some embodiments, the surface polymer comprises residues of one or more free radically polymerizable organosilane monomers.
[0073] Specific examples of free radical polymerizable organosilane monomers include unsaturated organosilane monomers (e.g., unsaturated organoalkoxysilane monomers, unsaturated organochlorosilane monomers, etc.), such as alkenyl or alkynyl functionalized organosilane monomers (e.g., alkenyl or alkynyl functionalized organoalkoxysilane monomers, alkenyl or alkynyl functionalized organochlorosilane monomers, etc.). Specific alkenyl functionalized organoalkoxysilane monomers include those having vinyl groups, methacryloxy groups, and acryloxy groups. Specific examples include 3-(trimethoxysilyl)propyl methacrylate (also known as 3-methacryloxypropyltrimethoxysilane or MAPTMOS), methacryloxypropyltriethoxysilane, methacryloxypropyltrichlorosilane, vinyltriethoxysilane (VTES), vinyltrimethoxysilane, N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane, (3-acryloxypropyl)trimethoxysilane, O-(methacryloxyethyl)-N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane, -(triethoxysilylpropyl)urethane, N-(3-methacryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane, methacryloxymethyltriethoxysilane, methacryloxymethyltrimethoxysilane, methacryloxypropylmethyldiethoxysilane, methacryloxypropylmethyldimethoxysilane, methacryloxypropyltri(methoxyethoxy)silane, 3-(N-phenylvinylmethyl-2-aminoethylamino)propyltrimethoxysilane hydrochloride, etc.
[0074] In a specific embodiment of the method for forming a surface-modified nonporous organic polymer core, an organosilane polymer, specifically a poly(styryl-C1-C4-alkyl-tri-C1-C4-alkoxysilane), is formed by copolymerizing a styryl-C1-C4-alkyl-tri-C1-C4-alkoxysilane monomer (wherein R is a C1-C4 alkyl) with a residual vinyl group (e.g., a residue of divinylbenzene) on the nonporous organic polymer core. Examples of styryl organosilane monomers include styrylethyltrimethoxysilane and styryltrimethoxysilane.
[0075] Organic-inorganic hybrid nonporous materials .
[0076] As previously mentioned, the present disclosure relates to nonporous particles in which a modified surface of a nonporous polymer core is in contact with a nonporous organic-inorganic hybrid material. The nonporous organic-inorganic hybrid material may be deposited or grown on the modified surface.
[0077] In some embodiments, the nonporous organic-inorganic hybrid material may have a thickness in the range of, for example, 1 nm to 4 microns, typically 25 nm to 200 nm. In some embodiments, the nonporous organic-inorganic hybrid material may have a pore volume of, for example, less than 0.10 cc / g (e.g., 0.05 cc / g), typically less than 0.02 cc / g.
[0078] "Organic-inorganic hybrid" materials include inorganic-based structures in which organic functional groups are integrated with both the internal or "framework" inorganic structure and the surface of the hybrid material. The inorganic portion of the hybrid material can be, for example, silicon dioxide, aluminum oxide, titanium, cerium or zirconium or their oxides, or a ceramic material. Exemplary hybrid materials are shown in U.S. Patents 4,017,528, 6,528,167, 6,686,035, 7,175,913 and 7,919,177, the disclosures of which are hereby incorporated in their entirety.
[0079] In some embodiments, the nonporous organic-inorganic hybrid material may include a silicon-based organic-inorganic hybrid material, which includes a hybrid region, wherein the silicon-based organic-inorganic hybrid material includes a silicon atom having one or more silicon-oxygen bonds and one or more silicon-carbon bonds. In some cases, the hybrid region may include a substituted or unsubstituted alkylene, alkenylene, alkynylene or arylene moiety bridging two or more silicon atoms. For example, the hybrid region may include a substituted or unsubstituted C1-C18 alkylene, C2-C18 alkenylene, C2-C18 alkynylene or C6-C18 arylene moiety bridging two or more silicon atoms. In some embodiments, the hybrid region may include a substituted or unsubstituted C1-C6 alkylene moiety bridging two or more silicon atoms, including a methylene, dimethylene or trimethylene moiety bridging two silicon atoms. In some embodiments, the hybrid region may include a ≡Si-(CH2)n-Si≡ portion, where n is an integer and may be equal to 1, 2, 3, 4 or greater. In some embodiments, the nonporous organic-inorganic hybrid material may include a silicon-based organic-inorganic hybrid material that includes an inorganic region in which the material includes silicon atoms having four silicon-oxygen bonds in addition to a hybrid region in which the material includes silicon atoms having one or more silicon-oxygen bonds and one or more silicon-carbon bonds.
[0080] In various embodiments, the nonporous organic-inorganic hybrid material can be formed by hydrolytic condensation of one or more organosilane compounds on a surface modified nonporous organic polymer core such as those described above. As used herein, an organosilane compound is a silane compound having at least one Si-C bond.
[0081] The organosilane compound may include, for example, (a) one or more organosilane compounds of the formula SiZ1Z2Z3Z4, wherein Z1, Z2, Z3 and Z4 are independently selected from Cl, Br, I, C1-C4 alkoxy, C1-C4 alkylamino and C1-C4 alkyl, wherein at least one of Z1, Z2, Z3 and Z4 is C1-C4 alkyl, examples of which include alkyl-trialkoxysilanes, such as C1-C4-alkyl-tri-C1-C4-alkoxysilanes, including methyltriethoxysilane, methyltrimethoxysilane, ethyltrimethoxysilane or ethyltriethoxysilane, and dialkyl-dialkoxysilanes, such as C1-C4-dialkyl-di-C1-C4-alkoxysilanes, such as dimethyldiethoxysilane, dimethyldimethoxysilane, diethyldimethoxysilane or diethyldiethoxysilane. and many other possibilities, and / or (b) one or more organosilane compounds of the formula Z1Z2Z3Si—R—SiZ4Z5Z6, wherein Z1, Z2 and Z3 are independently selected from Cl, Br, I, C1-C4 alkoxy, C1-C4 alkylamino and C1-C4 alkyl, but at most two of Z1, Z2 and Z3 can be C1-C4 alkyl, wherein Z4, Z5 and Z6 are independently selected from Cl, Br, I, C1-C4 alkoxy, C1-C4 alkylamino and C1-C4 alkyl, but at most two of Z4, Z5 and Z6 can be C1-C4 alkyl, and wherein R is an organic group, for example selected from C1-C18 alkylene, C2-C18 alkenylene, C2-C18 alkynylene or C6-C18 arylene, typically C1-C4 alkylene, typically C1-C6 alkylene. Examples of compounds of the formula Z1Z2Z3Si—R—SiZ4Z5Z6 include bis(trialkoxysilyl)alkanes, for example, bis(tri-C1-C4-alkoxysilyl)C1-C4-alkanes such as bis(trimethoxysilyl)methane, bis(trimethoxysilyl)ethane, bis(triethoxysilyl)methane and bis(triethoxysilyl)ethane as well as many other possibilities.
[0082] In some embodiments, one or more additional non-organosilane compounds can be hydrolyzed and condensed with one or more organosilane compounds. Such compounds include silane compounds of formula SiZ1Z2Z3Z4, wherein Z1, Z2, Z3 and Z4 are independently selected from Cl, Br, I, C1-C4 alkoxy and C1-C4 alkylamino. In certain embodiments, the additional silane compound is tetra-C1-C4-alkoxysilane, such as tetramethoxysilane or tetraethoxysilane.
[0083] In some embodiments, the nonporous organic-inorganic hybrid material can be formed by hydrolytic condensation of the following substances on the surface-modified nonporous organic polymer core as described above: (a) one or more alkoxysilanes, such as tetraalkoxysilanes (e.g., tetramethoxysilane (TMOS), tetraethoxysilane (TEOS), etc.), and (b) one or more organosilanes, for example, selected from bis(trialkoxysilyl)alkanes (e.g., bis(trimethoxysilyl)methane, bis(trimethoxysilyl)ethane, bis(triethoxysilyl)methane, bis(triethoxysilyl)ethane (BTEE), etc.) and / or alkyltrialkoxysilanes (e.g., methyltrimethoxysilane, methyltriethoxysilane (MTOS), ethyltriethoxysilane, etc.). In the case where the plurality of silane compounds includes one or more bis(trialkoxysilyl)alkanes, an alkyl-bridged organic-inorganic hybrid material is prepared, which can provide various advantages over conventional silica-based materials, including chemical and mechanical stability. When BTEE is used as a monomer, the resulting material is an ethylene bridged hybrid (BEH) material. A specific BEH material can be formed by the hydrolytic condensation of TEOS and BTEE.
[0084] In some embodiments, a plurality of silane compounds as described above (e.g., a plurality of silane compounds comprising one or more organosilanes and one or more tetraalkoxysilanes) are partially condensed to form a polyalkoxyorganosiloxane oligomer, which is then hydrolyzed and condensed onto the surface-modified nonporous organic polymer core. For example, BTEE and TEOS may be partially condensed to form a polyethoxyorganosiloxane oligomer (PEOS), which is hydrolyzed and condensed onto the surface-modified nonporous organic polymer core.
[0085] In various embodiments, the nonporous organic-inorganic hybrid material can be formed by producing (usually in a series of steps) a reaction mixture comprising the following components: a surface-modified nonporous organic polymer core, ethanol, one or more silanes (including one or more organosilanes as described above (e.g., TEOS and BTEE, or PEOS)), water, and a basic or acidic catalyst, the catalyst being used to promote the hydrolysis and condensation of the silanes of the nonporous organic-inorganic hybrid material on the surface-modified nonporous organic polymer core. In some embodiments, the hydrolysis is carried out at room temperature. In some embodiments, the mixture can be heated to drive the hydrolysis reaction to completion. In some embodiments, the mixture is stirred. After the nonporous organic-inorganic hybrid material is formed, the resulting particles can be washed and dried.
[0086] In other embodiments, nonporous organic-inorganic hybrid materials can be formed by the interaction between a template surfactant (e.g., and an ionic surfactant such as hexadecyltrimethylammonium bromide (CTAB) or trioctylmethylammonium bromide (TOMB)) and one or more silanes (including one or more organosilanes as described above (e.g., TEOS and BTEE, or PEOS)) during the continuous addition of silanes, alkaline catalysts, and template surfactants to a surface-modified nonporous organic polymer core. The process results in continuous silane hydrolysis and condensation of organic-inorganic hybrid reaction products on the core. The reaction can be carried out at room temperature or elevated temperature.
[0087] As described above, one or more organosilanes (e.g., TEOS and BTEE, or PEOS) can be hydrolyzed in the presence of a surface-modified nonporous (NP) organic polymer core having a surface polymer including monomer residues of an amide monomer and / or a silane monomer, such that the hydrolyzed organosilanes form a nonporous organic-inorganic hybrid material on the core.
[0088] Potential advantages of the disclosed nonporous composite particles include improved mass transfer and increased efficiency relative to conventional silica-based nonporous particles, as well as increased pH stability. The nonporous composite particles of the present technology can be used as chromatographic packing materials for separation of small molecules and large biologics.
[0089] Bonding material .
[0090] As previously described, the present disclosure relates to nonporous composite particles in which a binding material is in contact with a nonporous organic-inorganic hybrid material, which is in contact with a modified surface of a nonporous polymer core. The modified surface of the nonporous polymer core, the nonporous organic-inorganic hybrid material, or a combination thereof may include a binding material. For example, the modified surface and / or the nonporous organic-inorganic hybrid material may be modified with a binding material. The modification may be an intrinsic modification (i.e., the binding material is included when depositing or growing the material 120 or 130), a surface modification (i.e., the modification is applied to an exposed surface), or a combination thereof. For example, Figure 1A and Figure 1B As shown, in embodiment 100, the nonporous organic-inorganic hybrid material 130 can be surface-modified with a bonding material 140 to form a layer or region extending from the nonporous organic-inorganic hybrid material 130. In some cases, the bonding material 140 is covalently bonded or electrostatically bonded to the nonporous organic-inorganic hybrid material 130. In some cases, the bonding material 140 can have a thickness in a range of 0.1 nm to 200 nm. Figure 1B Shows Figure 1A1 is an enlarged view of the BB portion of the nonporous composite particle. It can be seen from the BB that the modified surface 120 of the nonporous polymer core 110 is in contact with the nonporous organic-inorganic hybrid material 130, and the bonding material 140 is in contact with the nonporous organic-inorganic hybrid material 130.
[0091] In another example, and if Figure 2A , Figure 2B and Figure 2C As shown, in an embodiment of the particle 200, the nonporous organic-inorganic hybrid material 230 is internally modified, wherein the binding material 240 partially (uniformly or in a gradient) extends through the nonporous organic-inorganic hybrid material 230. Even after the growth of the nonporous organic-inorganic hybrid material 230 has stopped, the binding material 240 can continue to be added to increase the functionalization or include different functionalization to the outermost surface of the nonporous composite particle 200. In some embodiments, the binding material 240 extending within the nonporous organic-inorganic hybrid material 230 is the same as the binding material added after the growth of the nonporous organic-inorganic hybrid material 230. However, this need not be the case. In some embodiments not shown, the binding material 240 within the nonporous organic-inorganic hybrid material 230 is different from the binding material extending through the nonporous organic-inorganic hybrid material (e.g., end caps are provided outside the material 230, or charges are added to create a charged surface).
[0092] Figure 2B Shows Figure 2A 2 is an enlarged view of the CC portion of the nonporous composite particle of FIG. From CC, it can be seen that the modified surface 220 of the nonporous polymer core 210 is in contact with the nonporous organic-inorganic hybrid material 230, and the bonding material 240 is in contact with the nonporous organic-inorganic hybrid material 230. Although not shown, in other embodiments, the nonporous organic-inorganic hybrid material 230 can be intrinsically modified, wherein the bonding material 240 extends completely through the nonporous organic-inorganic hybrid material 230.
[0093] Notice, Figure 2B This is for illustration only. When incorporated into the nonporous organic-inorganic hybrid material 230, the bonding material 240 is typically deposited discontinuously to produce bonding material "strands" extending radially throughout the thickness of the nonporous organic-inorganic hybrid material 230. However, the bonding material 240 may extend into a portion of the thickness of the nonporous organic-inorganic hybrid material 230. In certain preferred embodiments, the "units" (i.e., ligands) of the bonding material are incorporated and distributed within at least a portion of the nonporous organic-inorganic hybrid material 230. See, e.g. Figure 2C, wherein the binding material 240b is distributed within (i.e., intrinsically modified) the nonporous organic-inorganic hybrid material 230, and the binding material 240a is bound to the surface of (i.e., surface modified) the nonporous hybrid organic-inorganic material 230. The concentration or content of the binding material 240b within the nonporous organic-inorganic hybrid material 230 may be uniform throughout its thickness, or may be applied in a gradient form, and may also be exposed on the surface of the nonporous composite particles.
[0094] In yet another example, and if Figure 3A and Figure 3B As shown, in an embodiment of the particle 300, the modified surface 320 and the nonporous organic-inorganic hybrid material 330 are intrinsically modified with a binding material 340. That is, the binding material 340 at least partially extends through the modified surface 330, extends completely through the nonporous organic-inorganic hybrid material 330, and further surface-modifies the nonporous organic-inorganic hybrid material 330. Figure 3B Shows Figure 3A 3 is an enlarged view of the DD portion of the nonporous composite particle of FIG. As can be seen from the DD, the modified surface 320 of the nonporous polymer core 310 is in contact with the nonporous organic-inorganic hybrid material 330, and both the modified surface 320 and the nonporous organic-inorganic hybrid material 330 are in contact with the binding material 340. Although not shown, in other embodiments, the modified surface 320 can be intrinsically modified, wherein the binding material 340 extends completely through the modified surface 320, the nonporous organic-inorganic hybrid material 330 can be intrinsically modified, wherein the binding material 340 extends partially through the nonporous organic-inorganic hybrid material 330, or a combination thereof. It should be noted that even if the binding material is Figure 3B denoted as "strands" in FIG. 1 , the bonding material 340 is also included as a "unit", such as Figure 2C The binding material 340 can be the same material, or in some embodiments not shown, the binding material 340 can vary in one or more regions of the particle 300 (e.g., a different binding material in the modified surface 320 than within the nonporous organic-inorganic hybrid material 330 than extending outwardly (away from the core 310) from the nonporous organic-inorganic hybrid material 330).
[0095] Other embodiments of nonporous composite particles are also within the scope of the present technology. Figures 1A to 3B The illustrated embodiment includes a nonporous organic-inorganic hybrid material, but particles according to the present technology need not include such a material. For example, Figure 4A and Figure 4B The illustrated non-porous composite particle 400 includes a non-porous polymer core 410 , a modified surface 420 (eg, a silyl-modified surface) of the non-porous polymer core 410 , and a binding material 440 .
[0096] Figure 4B Shows Figure 4A 1 is an enlarged view of the EE portion of the nonporous composite particle. As can be seen from the EE, the modified surface 420 of the nonporous polymer core 410 includes the binding material 440b (i.e., intrinsic modification) and the binding material 440a (i.e., surface modification). By surface modification or by intrinsic modification, the modified surface 420 may include the binding material 440b (i.e., no need for such as Figure 4B In embodiments that include intrinsic modification of the modified surface 420, the binding material may be included in a gradient.
[0097] The bonding material can be functionalized (e.g., customized or adjusted) for a specific chromatographic separation or mode (obstacle chromatography, HDC, IP-RPLC, ion exchange chromatography). In some cases, at least a portion of the bonding material is a silane. The bonding material can be hydrophobic, hydrophilic, positively and / or negatively charged, or a combination thereof. In some cases, at least a portion of the bonding material can be an ionizable silane. The bonding material can include, but is not limited to, alkyl (e.g., C4 to C20), polyethylene glycol, hydrophilic polymers based on acrylamide and (meth)acrylate, polar groups containing nitrides, nitriles, hydroxyls, negatively and / or positively charged groups, amino, chlorine or alkoxysilanes, or a combination thereof.
[0098] In some embodiments, the bonding material can be uniformly incorporated into the non-porous composite particles, the bonding material and the modified surface and / or the non-porous organic-inorganic hybrid material are deposited synchronously (i.e., intrinsic modification) and / or deposited after the modified surface and / or the non-porous organic-inorganic hybrid material is deposited, and / or the bonding material can be incorporated into the non-porous composite particles in a gradient form, wherein the bonding material is deposited after the deposition of the modified surface and / or the non-porous organic-inorganic hybrid material begins but before the deposition ends. In some embodiments, the concentration or amount of the bonding material of the modified surface and / or the non-porous organic-inorganic hybrid material can vary along the thickness of the surface and / or the material. In some cases, the bonding material can be incorporated into the silyl-modified surface of the non-porous polymer particle core in a gradient form using silane bonding. (See, for example, U.S. Patent Publication US2019 / 0322783). In some cases, at least a portion of the bonding material is silane. The bonding material can be hydrophobic, hydrophilic, positively charged and / or negatively charged or a combination thereof. In some cases, at least a portion of the bond material can be an ionizable silane.
[0099] As used herein, the term "gradient" refers to the composition of a particle as viewed from the center of the particle to the surface of the particle. In a gradient material, the composition of the material varies based on the order and concentration of monomers added in a predetermined pattern, such that there is a compositional variation along the radius of the particle, but no discrete shell of material is formed. For example, a material of a polymer particle may have a unique gradient composition across the radius from the particle core to the outermost surface, wherein the compositional gradient includes, but is not limited to, a hydrophobicity / hydrophilicity gradient, a crosslinking ratio gradient, a functional group gradient, a charge ratio gradient, a density gradient, or a combination thereof.
[0100] In some embodiments, divinylbenzene can be used to synthesize nonporous polymer particle cores. For example, the surface of the divinylbenzene particle core can be modified with styrene trimethoxysilane. In some cases, the modified divinylbenzene particle core surface can then be coated with an ethylene bridge hybrid (organic-inorganic hybrid) compound and combined to obtain alkaline stable particles for chromatographic biomolecule separations.
[0101] In some embodiments, a method for separating large macromolecules is provided. The method may include using non-porous composite particles as disclosed herein to perform one or more of the following on large macromolecules (such as DNA, nucleic acids, proteins, and macromolecular complexes thereof): barrier chromatography, hydrodynamic chromatography, reverse phase chromatography, hydrophilic interaction chromatography, ion exchange chromatography, or mixed mode chromatography.
[0102] Potential advantages of the nonporous composite particles of the present disclosure include improved mass transfer and increased efficiency relative to nonporous particles, and increased pH stability.The nonporous composite particles can be used as chromatographic packing materials for separation of small molecules and large biologics.
[0103] Chromatographic device .
[0104] In some aspects of the present disclosure, the non-porous composite particles described herein can be provided in a suitable chromatographic device. For this reason, the non-porous composite particles described herein can be provided together with a suitable housing. The non-porous composite particles and the housing can be supplied independently, or the non-porous composite particles can be pre-packaged in the housing. The housing used according to the present disclosure generally includes a chamber for receiving and holding non-porous composite particles. In various embodiments, the housing can be provided with an inlet and an outlet leading to the chamber and leading out from the chamber.
[0105] Suitable materials of construction for the chromatography housing include inorganic materials, for example, metals such as stainless steel and ceramics such as glass, and synthetic polymeric materials such as polyethylene, polypropylene, polyetheretherketone (PEEK), and polytetrafluoroethylene, among others.
[0106] In certain embodiments, the chromatography housing may include one or more filters for retaining the non-porous composite particles in the housing. Exemplary filters may be in the form of, for example, a membrane, a mesh, a frit, or a spherical porous filter.
[0107] In certain embodiments, the chromatographic device is a chromatographic column.
[0108] The present disclosure also provides a kit comprising a nonporous composite particle, a housing or a device as described herein, and instructions for use. In one embodiment, the instructions are for a separation device, such as a chromatography column.
[0109] Chromatographic separation .
[0110] In some aspects of the present disclosure, the non-porous composite particles of the present disclosure can be used for a variety of chromatographic separation methods. Therefore, chromatographic devices and chromatographic suits described herein can also be used for such methods. The example of the chromatographic separation method of the non-porous composite particles of the present invention can be used includes being used for high pressure liquid chromatography (HPLC) and ultra-high pressure liquid chromatography (UHPLC) in different modes. Those modes include but are not limited to affinity separation, hydrophilic interaction chromatography (HILIC) separation, normal phase separation, reversed phase separation, chiral separation, supercritical fluid chromatography SFC separation, perfusion separation, size exclusion chromatography (SEC) separation, ion exchange separation or multi-mode separation.
[0111] The non-porous composite particles, devices and kits disclosed herein can be used for chromatographic separation of substances such as small molecules, carbohydrates, antibodies, whole proteins, peptides and / or DNA.
[0112] Such chromatographic separations may include loading a sample onto the non-porous composite particles according to the present disclosure, and eluting the adsorbed species from the non-porous composite particles with a mobile phase.
[0113] Such chromatographic separations can be performed in conjunction with a variety of aqueous and / or organic mobile phases (i.e., in mobile phases containing water, organic solvents, or a combination of water and organic solvents) and in conjunction with a variety of mobile phase gradients (including gradients of solvent type, temperature, pH, salt concentration, or other parameters).
[0114] The following examples are provided to illustrate how to make composite particles and components thereof according to the present technology. These examples are for illustrative purposes only and should not be considered restrictive. When an amount, concentration or other value or parameter is given as a list of ranges, preferred ranges or upper preferred values and lower preferred values, it should be understood that all ranges formed by any pair of any upper range limit or preferred value and any lower range limit or preferred value are specifically disclosed, regardless of whether the range is disclosed separately. In the case of numerical ranges listed herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within the range. When limiting the range, the scope of the present technology is not intended to be limited to the specific value described.
[0115] Example 1: Preparation of non-porous particles for bioseparation
[0116] In this example, exemplary non-porous composite particles are produced that are particularly advantageous in the separation of biomolecules. Other methods and other materials can be utilized to produce non-porous composite particles of the present technology.
[0117] Granule nucleosynthesis In the particle core synthesis, nonporous divinylbenzene 80% (DVB80) core particles were synthesized in ethanol by free radical polymerization using azobisisobutyronitrile (AIBN) as an initiator. The core was pretreated using styrene monomer with terminal trimethoxysilane groups and DVB by copolymerization with residual side C=C double bonds on the core surface. 1.5 SiCH2CH2SiO 1.5 ) 0.25 The surfaces of inorganic-organic ethylene-bridged hybrids (BEHs) were further modified to obtain nonporous, chemically stable particles that can be used as as-prepared chromatographic stationary phases or further functionalized for alternative modes of chromatographic separations.
[0118] Table 1 below presents various materials formed using similar procedures as described above. Specifically, the procedure of Example 1 details how to make Material 1C, a DVD with silanized surface particles coated with BEH. In order to compare Material 1C with other non-porous particles, the inventors also made Material 1A (DVB particles) and Material 1B (DVB particles with silanized surfaces).
[0119] Material Nuclear particle description <![CDATA[Surface area of nuclear particles (m 2 / g)]]> 1A DVB 1.7 1B DVB with silanized surface 2.0 1C Surface silanized DVB coated with BEH 2.4
[0120] Table 1
[0121] Surface functionalization (bonding): Under anhydrous conditions, amino, chloro or alkoxy silane (8 μmol / m 2 -200 μmol / m 2) The nonporous DVB80 particles described above were further modified with and without catalysts (imidazole, HCl) in toluene to obtain surfaces for a variety of chromatographic separation modes (obstacle chromatography, HDC, IP-RPLC, WAX). That is, the fluid contacting surface of the nonporous composite particles was tailored with materials tuned for a specific separation mode.
[0122] Hydrophilic surface The nonporous DVB 80 particles modified with the bridged-ethylene hybrid as described above were further modified using hydroxyl-terminated polyethylene glycol (HO-PEG) silane to obtain a hydrophilic surface. To form this surface, the NP DVB particles were dispersed in toluene (10 mL / g) under anhydrous conditions. Concentrated hydrochloric acid (20 μL / g particles) was added, followed by [hydroxy(polyethyleneoxy) 8-12 propyl]triethoxysilane (HO-PEG; 200 μmol / m 2 ). The reaction was heated to 110°C for 20 hours and then cooled to RT. The particles were isolated via filtration and subsequently washed with toluene, ethanol and water.
[0123] After the bonding reaction, the remaining ethoxysilyl groups were hydrolyzed using ammonium bicarbonate (100 mM) at 100°C for 3 hours. The reaction was cooled to RT and the particles were isolated by filtration. The particles were then washed with water to reduce the pH to <6, then washed with acetone, and then dried in vacuo at 70°C for 16 hours.
[0124] Hydrophobic surface : The nonporous DVB 80 particles modified with the bridged-ethylene hybrid as described above were further modified with alkylsilanes to obtain a hydrophobic surface. To form this surface, 8 μmol / m 2 NP DVB particles were dispersed in toluene (10 mL / g) with butyldimethyl(dimethylamino)silane (mC4) or octyldecyltrichlorosilane (tC18). Catalyst (imidazole; 10 μmol / m 2 ) was added together with octyldecyltrichlorosilane. The reaction was heated to 110°C for 20 hours and then cooled to RT. The particles were separated by filtration and then washed with toluene, acetone and water. After the bonding reaction, the trifunctional C18 phase was hydrolyzed at 50°C for 2 hours using ammonium bicarbonate (100mM) and acetone (40:60v / v). The reaction was cooled to RT and the particles were separated by filtration. The particles were then washed with toluene, acetone and water and then dried in vacuo at 70°C for 16 hours.
[0125] The remaining surface silanols were capped with hexamethyldisilazane (HMDS; neat, 200 °C, 20 h) or (N,N-dimethylamino)triethylsilane (TES; 5 μmol / m 2) and (N,N-dimethylamino)trimethylsilane (TMS; 8 μmol / m 2 ) was capped in toluene (10 mL / g) at 110° C. for 4 hours. The particles were isolated by filtration, then washed with toluene, acetone and water, and dried in vacuo at 70° C. for 16 hours.
[0126] Charged surface The nonporous DVB 80 particles modified as described above to have a phenyl-silanized surface or a bridged-ethylene hybrid surface were further modified using an ionizable silane to obtain a charged surface. To form this surface, bispropylmethylaminotrimethoxysilane (BPMA; 8 μmol / m 2 ) NP DVB particles were dispersed in toluene (10 mL / g). The reaction was heated to 110°C for 20 hours and then cooled to RT. The particles were isolated by filtration and then washed with toluene, acetone and water and then dried under vacuum at 70°C for 16 hours.
[0127] Table 2 below presents various materials formed using similar procedures as described above. Specifically, the procedure of Example 1 details how to functionalize the surface of material 1C to prepare materials 2C-2F. In order to compare materials 2C-2F with other non-porous particles, the inventors also made material 2A (silanized DVB particles with bridged-ethylene hybrid surfaces) and material 2B (DVB particles with silanized surfaces).
[0128]
[0129] Table 2
[0130] Example 2: Size-based separation / barrier separation of DNA using BEH-DVB particle columns and Tris-buffered saline mobile phase Impedance Chromatography
[0131] In this example, the nonporous composite particles are used for chromatographic separation prior to adding or forming the bonding material disclosed herein. Based on the techniques described herein, other methods and other materials can be used to perform such chromatographic separation.
[0132] Obstacle chromatography is a form of fractionation that was first described by Hirabayashi et al. in 1990. Figure 5 A schematic diagram of the flow dynamics found to occur when a nucleic acid sample is injected onto a packed bed of non-porous particles is presented. In this separation, flow dynamics, entropy, and physical filtering phenomena cause smaller nucleic acids to elute before larger nucleic acids.
[0133] Example 3: Barrier Chromatography of DNA Using BEH-DVB Particle Column
[0134] In this example, nuclease treated lambda phage DNA was subjected to barrier chromatography prior to addition or formation of the binding material disclosed herein. Here, a larger volume was injected for peak fractionation and to facilitate secondary analysis based on charge detection mass spectrometry and pulsed field gel electrophoresis.
[0135] Untreated λ phage DNA and nuclease-treated λ phage DNA were obtained from New England Biolabs (N3011 and N3019; Ipswich, MA). The samples were chromatographed at room temperature using an Acquity Premier LC and a 4.6 mm × 300 mm column constructed with a hydrophilic high-performance surface hardware component and BEH-DVB particles (Material 1C). Ammonium formate at pH 7.4 was used as the mobile phase. The flow rate was 0.2 mL / min, the injection volume was 5 μL, and UV detection was 260 nm. The chromatographic results of the nuclease-treated λ phage DNA sample are presented in Figure 6 The same particles (Material 1C) were used in a chromatographic separation similar to that provided above, but instead of using ammonium formate as the mobile phase, phosphate buffered saline (PBS) at pH 7.4 was used. The results were Fig. 7A and Figure 7B Provided in Fig. 7A Provide gel electrophoresis results and chromatography results of nuclease-treated lambda phage DNA samples, and Figure 7B Chromatograms of untreated samples are provided.
[0136] Example 4: Ion-paired reversed-phase chromatography of nucleic acids using C18 BEH DVB particles
[0137] In this example, ion-paired reverse phase chromatography was performed using C18-bound BEH-coated silanized DVB particles. Based on the techniques described herein, other methods and other materials can be used to perform this chromatographic separation.
[0138] A column containing reverse phase C18-bound BEH-coated silanized DVB particles (Material 2F, Table 2 above) was prepared and used for ion-paired reverse phase liquid chromatography (IP-RPLC) separation of deoxythymidine oligomers. The particles were packed into a 2.1 mm×150 mm stainless steel column at a flow rate of 0.3 mL / min at 60°C. Mobile phase A included 110 mM octylammonium acetate in 40% acetonitrile, and mobile phase B included 110 mM octylammonium acetate in 95% acetonitrile. 20 pmol-50 pmol of sample was injected, where the sample was 20 nt, 30 nt, 40 nt, 50 nt, 60 nt, 80 nt and 100 nt of oligo deoxythymidine. The gradient was 0 to 72.7% B (40%-80% acetonitrile) and 2% acetonitrile / minute in 20 minutes. The results were Figure 8 Available in.
[0139] Example 5: Size-Based Separation / Barrier Chromatography of Nucleic Acids Using HO-PEO-Conjugated BEHDVB Particles
[0140] Columns prepared with HO-PEO-bound BEH DVB particles (Material 2D) were used for size-based separation of large nucleic acid species. HO-PEO-bound BEH DVB particles (2.2 μm) were packed into a 2.1 mm × 300 mm column constructed with a hydrophilic high-performance surface hardware component. See US2022-0118443, which describes a C2PEG coating for providing a hydrophilic chromatographic component, and the entire contents of which are incorporated herein by reference. The separation conditions were as follows: isocratic at room temperature, a flow rate of 0.04 mL / min, and a PBS pH of 7.4. The separation of the sample was evaluated using a TUV detector at 260 nm (0.2 μL of λDNA single-cut mixture from New England BioLabs, Inc., Ipswich, MA). The chromatographic results of this example are Fig. 9 Depicted in.
[0141] Example 6: Weak anion exchange of nucleic acids
[0142] In this example, chromatographic separations were performed using the exemplary nonporous composite particles disclosed herein. Based on the techniques described herein, other methods and other materials can be used to perform such chromatographic separations.
[0143] Columns prepared with weak anion exchange (WAX) BEH DVB particles are used for ion exchange-based separation of large nucleic acid materials. In this example, BPMA-bound BEH DVB particles (Material 2C, Table 2) were filled into a 2.1 mm × 50 mm stainless steel column constructed from hydrophilic high-performance surface hardware components. Several different separation techniques were applied, including salt gradients, ion-paired anion exchange (IPAX) and pH gradients and their combinations. For pH gradient chromatography, the gradient composition delivery was empirically corrected using the online effluent pH response, thereby generating a linear pH gradient for all applied mobile phase compositions. Complete and nuclease-treated lambda bacterial phase DNA, as well as complete mRNA and nuclease-digested mRNA were separated. The following experimental conditions were used for separation on an Acquity Premier Quaternary LC system (Waters Corporation, Milford, MA), with an injection volume of 1 μL and a flow rate of 0.2 mL / min. The column temperature was room temperature. Mobile phase A was 20 mM Tris, pH 7.5, and mobile phase B was 20 mM Tris, pH 7.5, containing 1 M NaCl. A mobile phase gradient of 2% to 80% B in 25 min was applied. A UV detector (260 nm) was used to monitor the separation.
Claims
1. A non-porous composite particle, comprising: a nonporous polymer particle core having a silyl-modified surface; a nonporous organic-inorganic hybrid material in contact with the silyl-modified surface; and A bonding material is in contact with the nonporous organic-inorganic hybrid material.
2. The particle of claim 1 wherein the nonporous polymer particle core comprises 80% divinylbenzene.
3. The particle of claim 1, wherein at least a portion of the nonporous organic-inorganic hybrid material is bonded to the silyl-modified surface of the nonporous particle core via silane bonding.
4. The particle of claim 1, wherein at least a portion of the nonporous organic-inorganic hybrid material is a silane to form a functionalized surface.
5. The particle of claim 4, wherein the functionalized surface of the nonporous organic-inorganic hybrid material is hydrophilic.
6. The particle of claim 4, wherein the silane comprises hydroxyl terminated polyethylene glycol (HO-PEG) silane.
7. The particle of claim 1, wherein at least a portion of the nonporous organic-inorganic hybrid material is an alkyl silane to form a functionalized surface.
8. The particle of claim 7, wherein the functionalized surface of the nonporous organic-inorganic hybrid material is hydrophobic.
9. The particle of claim 1, wherein at least a portion of the nonporous organic-inorganic hybrid material is an ionizable silane to form a functionalized surface.
10. The particle of claim 9, wherein the functionalized surface of the nonporous organic-inorganic hybrid material is charged.
11. The particle of claim 1, wherein the silyl-modified surface of the nonporous polymer particle core comprises a first functional group and a second functional group, the first functional group comprising a reactive silane and the second functional group comprising an organic polymerizable group.
12. The particle of claim 11, wherein the reactive silane comprises an alkoxy group.
13. The particle of claim 11, wherein the organic polymerizable group comprises a vinyl group.
14. A non-porous composite particle, comprising: a nonporous polymer particle core having a silyl-modified surface; as well as A binding material is in contact with the silyl-modified surface of the nonporous polymer particle core.
15. The particle of claim 14, wherein the non-porous polymer particle core comprises divinylbenzene (80%).
16. The particle of claim 14, wherein at least a portion of a binder material is bonded to the modified surface of the nonporous particle core via silane-based bonding.
17. The particle of claim 14, wherein at least a portion of the binding material is a silane to form a functionalized surface.
18. The particle of claim 17, wherein the functionalized surface is hydrophilic.
19. The particle of claim 14, wherein at least a portion of the binding material is an alkyl silane to form a functionalized surface.
20. The particle of claim 19, wherein the functionalized surface of the binding material is hydrophobic.
21. The particle of claim 15, wherein at least a portion of the bonding material is an ionizable silane to form a functionalized surface.
22. The particle of claim 21, wherein the functionalized surface of the binding material is charged.
23. The particle of claim 14, wherein the silyl-modified surface of the nonporous polymer particle core comprises a first functional group and a second functional group, the first functional group comprising a reactive silane and the second functional group comprising an organic polymerizable group.
24. The particle of claim 23, wherein the reactive silane comprises an alkoxy group.
25. The particle of claim 23, wherein the organic polymerizable group comprises a vinyl group.
Citation Information
Patent Citations
Polymer particles with a gradient composition and methods of production thereof
US20190322783A1
Device including a hydrophilic, non-ionic coating for size exclusion chromatography
US20220118443A1
Preparation of organically modified silicon dioxides
US4017528A
Porous hybrid particles with organic groups removed from the surface
US6528167B2
Porous inorganic / organic hybrid particles for chromatographic separations and process for their preparation
US6686035B2